V de Vingança, Jogos Vorazes e Fahrenheit 451 : o uso de distopias no ensino de história - Borges, Natália Moura (2021)
This dissertation aims to present the historical articulations of dystopia, present in the films V for Vendetta (2005, directed by James Mc Teigue), Voating Games (2012, directed by Gary Ross) and Fahrenheit 451 (2018, directed by Ramin Bahrani), for the teaching of History. Dystopia, as a cinematographic narrative, is inserted by problematizing a society controlled by the State, its extremes of oppression and how this can generate chaos for humanity. That said, it manages to represent verisimilitude with our surroundings, revealing ideological patterns and power structures persistent in contemporary times. The research course results from qualitative methodology, references and theoretical framework, such as those by Marc Ferro (1992), Marcos Napolitano (2003) and Robert Rosenstone (2010) about films, their relationship with history and learning, as well as for the reflection about the teaching of History found in the discussions of Circe Bittencourt (2011) and Elza Nadai (1993 and 2009), in the concept of conscience promoted through the praxis of action-reflection of the subjects, discussed by Paulo Freire (1979) and in the perception of historical consciousness defended by Jörn Rüsen (2001), for the examination of perspectives that base this pedagogical practice. The results of the investigation point to the favoring of making students pedagogically active in the historical debate and, for History teachers, an alternative tool associated with the teaching-learning approach. At the end of the work, a didactic sequence with procedures for the analysis of the films proposed here is presented as a pedagogical tool, and for culmination in an audiovisual production, with the aid of the Stop Motion Studio application. In order to offer support to facilitate its use, a written and audiovisual tutorial was made available, with step-by-step instructions for using this tool. Furthermore, the proposal of other film titles was added, expanding the possibilities of choice, considering different realities of school environments.